The Efficiency of Amalgamation and Cyanidation for the Extraction of Placer Gold Deposits of Indus River Basin along Gilgit to Thalachi (Gilgit-Baltistan): The Efficiency of Amalgamation and Cyanidation for the Extraction of Placer Gold Deposits of Indus River Basin along Gilgit to Thalachi (Gilgit-Baltistan) - Alam, Muhammad; Qureshi, Javed Akhter; Khan, Garee; Ali, Manzoor; Abbas, Naeem; Ali, Irfan (International Journal of Economic and Environmental Geology, 2019)
Separation of gold from placers are not given importance in Pakistan, but in the economy of Gilgit-Baltistan, it plays a vital role. The study mainly focused on shaking table technique for the extraction of gold from placer deposits along Gilgit river between Gilgit and Thalachi, near Gilgit and Astore river junction. For the separation of gold, from the concentration of shaking table the Hg; mercury amalgamation has been used for it. In the result of the amalgamation process recovered gold was 27.12%. The cyanidation process was used to separate from remains of mercury amalgamation, tailing and middling of shaking table. The graphical results of gold extraction with bottle roll cyanidation and agitation method were compared. The results of gold separation using bottle roll cyanidation and agitation methods were about 87.5% and 29.8% respectively. It is clear from the results, the bottle roll cyanidation is a better technique for the separation of fine gold from placers along with downstream waterway areas, where placer deposits occur.